Full-Genome Characterization of Simian T-Cell Leukemia Virus Type 1 Subtype b from a Wild-Born Captive Gorilla gorilla gorilla with T-Cell Lymphoma - Ayouba, Ahidjo (Genome Announc, 2017)
There are four lineages of primate T-cell lymphocytic viruses (human T-cell lymphocytic virus [HTLV]/simian T-cell lymphocytic virus [STLV]), which are further divided into subtypes. To date, there is only one full-length HTLV-1 subtype b genome available. Here, we report the genome of a new STLV-1 subtype b from a 43-year-old male gorilla with T-cell lymphoma.